Essai de reconstitution des agrosystèmes et des ressources alimentaires dans les monts Mandara (Cameroun) des premiers siècles de notre ère aux années 1930 - Christian Seignobos (Revue d'ethnoécologie)
Our intention in the present paper is to go back in time and lay out the history of eating and drinking in the Mandara Mountains. Located in the Chad Basin area, the Mandara Mountains often lag behind the neighbouring plains when it comes to the diffusion of plants, even though they did manage to maintain these crops over longer periods of time. Such an enclosed environment only allowed a selected vegetation to grow, from which specific and controled collecting methods have developed.These mountain dwellers have evolved together with their agrosystems over time. This history can be divided into three major periods. The first one is characterized by a mountain horticulture with yams, small tubers, gradually replaced by cereals such as eleusines and millets (Pennisetum glaucum), and finally ending in the Sorghum complex of the last past centuries. Since the remotest times, a set of crops focused on cowpeas (Vigna unguiculata) have allowed these diverse ways of moutain farming to develop. Such leguminous plants formed the basis of the local diet, irrespective of the associations and rotations of crops stemming from social or economic considerations.We have only been able here to point out probable successions of agricultural combinations which are now awaiting further investigations from other disciplines such as archaeology in order to be confirmed or not.